2014
DOI: 10.1007/s10096-014-2241-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of blaZ gene types and the cefazolin inoculum effect among methicillin-susceptible Staphylococcus aureus blood isolates and their association with multilocus sequence types and clinical outcome

Abstract: Cefazolin treatment failures have been described for bacteraemia caused by methicillin-susceptible Staphylococcus aureus (MSSA) with type A β-lactamase and inoculum effect (InE). We investigated the prevalence of blaZ (β-lactamase) gene types and a cefazolin InE among MSSA blood isolates in South Korea and evaluated their association with specific genotypes. The clinical impact of the cefazolin InE was also evaluated. A total of 220 MSSA isolates were collected from a prospective cohort study of S. aureus bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
42
0
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 21 publications
2
42
0
3
Order By: Relevance
“…There are published reports (including from our group) that correlate the CFZ inoculum effect with clinical failure (4,5,7,14,16). These reports have shown that, in the majority of the strains, an increase in the CFZ MICs (tested at high inoculum) was associated with the presence of type A ␤-lactamase (4, 5, 7).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…There are published reports (including from our group) that correlate the CFZ inoculum effect with clinical failure (4,5,7,14,16). These reports have shown that, in the majority of the strains, an increase in the CFZ MICs (tested at high inoculum) was associated with the presence of type A ␤-lactamase (4, 5, 7).…”
Section: Discussionmentioning
confidence: 91%
“…This review states that, in addition, limited by small sample size and possible selection bias, the only comparative study to date examining the clinical impact of the cefazolin InE (i.e., the study referred to above from Asia [South Korea] [7]) did not show any significant differences in outcomes when comparing isolates with and without cefazolin InE. However, it is not clear what percentage of the patients had endocarditis or deep-seated and/or undrained infections, which would be more likely to have a large inoculum present.…”
mentioning
confidence: 99%
“…A 2009 study analyzing 98 MSSA isolates reported no blaZ for 13%, type A ␤-lactamase for 26%, type B for 15%, and type C for 46% (8). A South Korean study found type A blaZ in 17%, type B in 20%, type C in 53%, and type D in 1% of 220 MSSA isolates (12). Cefazolin failures have been reported for MSSA infections caused by type A blaZ isolate demonstrating an inoculum effect (8), but other retrospective studies have only found treatment success (12).…”
mentioning
confidence: 99%
“…A South Korean study found type A blaZ in 17%, type B in 20%, type C in 53%, and type D in 1% of 220 MSSA isolates (12). Cefazolin failures have been reported for MSSA infections caused by type A blaZ isolate demonstrating an inoculum effect (8), but other retrospective studies have only found treatment success (12). Prospective studies are needed to determine if screening MSSA isolates for a cefazolin inoculum effect has clinical utility.…”
mentioning
confidence: 99%
“…However, there are concerns about cefazolin therapeutic failures and relapses in the treatment of MSSA strains that demonstrate the CIE (2,3,20,21). Previous studies have demonstrated that the CIE in MSSA is closely associated with the blaZ type, and type A blaZ-positive MSSA can present a CIE (3,11,12,22,23). However, the prevalence of CIE positivity among MSSA strains positive for type A blaZ is variable, and approximately 15 to 65% of these strains exhibited no CIE (3,11,12,22,23).…”
mentioning
confidence: 99%